The rule of three - Cate, Sara (Cate, Sara. Salacious legacy, 2026)
"Three hearts. One consuming fire. Julian Kade hates everyone. But when a power outage traps him in a Paris elevator with sharp-tongued chef Freya Kapoor and charming street fighter Archer Wilde, an unexpected spark ignites between them. By the end of the twelve hours that follow, they've shared their darkest desires...and formed a bond none of them could have expected. Freya Kapoor has dreams, and getting sidetracked by two billionaires wasn't part of her careful plan. But when the two men who've begun to dominate her body and mind present Freya with a chance to open the restaurant of her dreams, boundaries quickly blur...and her orderly world gets increasingly complicated. Archer Wilde never thought he'd stop fighting long enough to get tangled up with two such different people. Yet the three of them fit together like nothing before, unlocking hidden desires they never knew they had. But beneath the perfect facade are three individuals battling demons of their own. Ultimately, as passion deepens into something far more dangerous, Freya, Julian, and Archer will have to choose whether they're willing to risk everything they've built for a love as fierce as it is free"-- Provided by publisher.